Oil Extract of Momordica charantia Seed (OEMCS) Exhibits Biphasic Effect on Blood Coagulation, Antiplatelet and Antioxidant Properties - Manjappa, Bhagyalakshmi; Sannaningaiah, Devaraja (Asian Journal of Biological and Life Sciences)
Aim: Extraction of Oil from Momordica charantia seed and its characterization. Materials and Methods: Oil was extracted from the dried seeds of Momordica charantia using Soxhlet apparatus with petroleum as a solvent at the temperature of 60°C for about 8 hr. Momordica charantia seed oil was characterized using GC-MS. anticoagulant, antiplatelet, and antioxidant assay toxicity studies were carried out. Results: The fatty acid profile obtained from GCMS suggested the presence of lipids at a fair percentage. (Saturated fats-38.67%, unsaturated fats-59.39% (MUFA- 1.56% and PUFA-57.83). The iodine value of extracted fatty acid was found to be 66.7 with a refractive index of 1.493 at 40°C. OEMCS exhibited a biphasic effect on plasma recalcification time. OEMCS showed a strong procoagulant effect at volume 1 to 10 μg by decreasing the clotting time from control 291 to 33sec. However, as the volume of oil was increased above 10μg it drastically shifted from pro-coagulation to anticoagulation by increasing the clotting time from 194 sec to 267 sec. Furthermore, the effect of OEMCS oil on platelet aggregation was analyzed using agonists such as ADP and epinephrine. Interestingly, OEMCS oil showed 44% and 97% platelet aggregation inhibition for ADP and Epinephrine in platelet-rich plasma. The antioxidant property of oil extract was tested by DPPH and LPO assays, OEMCS oil showed bleaching of DPPH absorption, reflecting on proton donating ability, and thereby free radical scavenging ability was confirmed. OEMCS decreased by 80% lipid peroxidation when compared with NaNo2-treated PRP alone at the highest dose of 150μg. OEMCS did not cause hemolysis to RBC, hemorrhage, and edema in experimental animals revealing its non-toxic nature. Conclusion: OEMCS exhibits a biphasic effect on plasma coagulation but shows strong antiplatelet and antioxidant activities. Meanwhile, it revealed non-toxic properties, thus OEMCS may prove to be a good natural therapeutic agent in oxidative stress and cardiovascular disorders.
Keywords: Anticoagulant; Antiplatelet and Antioxidant.; Oil extract; Platelet rich plasma